Ultrastructure of the sensilla on antennae and mouthparts of larval and adult Plutella xylostella (Lepidoptera: Plutellidae) - Yi-ping LI; Xiao DU; Fang-fang LIU; Yin LI; Tong-xian LIU (Journal of Integrative Agriculture)
Plutella xylostella (L.) (Plutellidae) is an important agricultural pest throughout the world. In this study, the morphology of antennal and mouthpart sensilla in the larvae and adults of P. xylostella (L.) was observed by using a scanning electron microscope. The larval antennae possess six sensilla basiconica, two sensilla chaetica and one sensillum styloconicum. Larval mouthparts possess six types of sensilla: sensilla chaetica, sensilla digitiformia, sensilla epipharyngeal, sensilla basiconica, sensilla styloconica and sensilla placodea. In the adult, seven types of sensilla are found on the antennae in males and six types of sensilla (sensilla basiconica absent) occur in females. Sexual dimorphism is also found in the number and size of these sensilla on the antennae of adults. We describe for the first time the five types of sensilla on the mouthparts of the adult of P. xylostella. This study provides useful information for further research into the function of these sensilla, and better understanding the behavioral mechanisms involved in pest control.